Invasion team sports: strategy and match modeling - Lamas, L.; Barrera, J.; Otranto, G.; Ugrinowitsch, C. (International Journal of Performance Analysis in Sport, 2014)
Performance in invasion team sports (ITS) is highly dependent on the appropriate execution of an efficient team strategy by the players. Strategy enables individual and group actions to be organized in order to produce collective execution, increasing the diversity and unpredictability of the team`s actions. Nonetheless, the scientific literature has mainly analyzed match events without integrating information regarding the observed behavioral patterns and team strategies. As neither match dynamics nor its relation with strategy has been modeled, this study accomplishes these goals through the following steps. First, the organization of collective play was defined by modeling the strategic control of players` actions and the coordination of cooperative actions between two or more players. Second, a model was constructed that supports the design of strategies, including constraints that ensure effective usefulness of the strategy. Third, the integration between the strategy model and the dynamical structure of the confront was established through the match model. The presented model may provide insight for team training, match analysis, support the development of intelligent software to help coaches design team strategies and as prior information about the collective movements of the team players acquired from automatic player recognition using digital video images.